The Parlêtre: Membaca Problematika Identitas Rocky Gerung Bersama Jacques Lacan: Parlêtre: Reading Rocky Gerung's Identity Problems With Jacques Lacan - Oktofianus Oki; Norbertus Jegalus; Leonardus Mali (Undiksha, 2026)
This article examines the issue of Rocky Gerung's identity through the perspective of Jacques Lacan's philosophy and psychoanalysis, particularly the concept of parlêtre or speaking being. This concept asserts that humans are essentially subjects formed through language. Lacan views language not merely as a tool of communication, but as a symbolic structure that shapes identity, conveys desire, and limits subjects in the symbolic realm. The research focuses on three aspects: the Lacanian identity paradigm, the construction of Rocky Gerung's identity, and the empowerment of his thinking in the public sphere. The research method used is a literature study analyzing Lacan's works, Rocky Gerung's writings, and various seminar materials and public content in the mass media. The results of the study show that Rocky Gerung's identity is a manifestation of a Lacanian subject that is unstable, fragmented, and empty. Language plays an important role in shaping this identity while also serving as a medium for channeling desires that are never fully realized. In conclusion, Rocky Gerung's identity is a linguistic construction that continues to move within the symbolic realm, reflecting the dynamics of the unconscious and the need for recognition, as well as affirming the relevance of Lacan's thinking in understanding contemporary social identity.